Effect of Biochar Amendment on the Growth and Photosynthetic Traits of Plants Under Drought Stress: A Meta-Analysis - Wenqian Zhang; Wenquan Niu; Huoqian Luo (Agronomy)
Biochar, as a soil improvement additive, is widely applied in field practices due to its excellent performance in improving soil conditions and promoting plant growth under drought stress. A meta-analysis was conducted, analyzing 283 pairs of non-biochar-amendment (non-BA) controls and biochar amendment (BA) treatments under drought stress. This study aims to (1) evaluate the effects of biochar on gas exchange and carbon accumulation in plants under drought stress; and (2) quantify the factors influencing biochar’s effects. The results showed that BA had a statistically significant positive impact on water use efficiency (WUE), yield, biomass, chlorophyll content, stomatal conductance (gws), photosynthetic rate (Pr), and transpiration rate (Tr). The extent of these effects was influenced by plant type, degree of water stress, soil type, and the duration of BA application. The response to BA varied across plant types, with significant effects on the WUE of legumes (32.4–37.7%) compared to modest effects on eggplants and other vegetables (8.1–9.4%). BA was more effective in improving plant growth and WUE in soils with extremely coarse or fine textures than in those with medium particle sizes. The duration of BA application was also a critical factor; as the application duration increased, the improvement rates of yield, chlorophyll content, gws, and photosynthetic rate showed a decreasing trend, while WUE and biomass did not exhibit significant declines. However, Tr increased sharply over time. These findings highlight the potential of BA to enhance plant growth, WUE, and photosynthetic traits, while identifying the conditions under which these benefits can be maximized.